2019
DOI: 10.3390/w11081646
|View full text |Cite
|
Sign up to set email alerts
|

Site Assessment for MAR through GIS and Modeling in West Coast, South Africa

Abstract: Towns along the West Coast of South Africa are facing water shortages due to climate change and increasing water demand. Managed aquifer recharge (MAR) is considered as a solution to improve water security. This paper presents a two-step method of combining geographic information system (GIS) based analysis with numerical modeling to select suitable sites for implementing MAR in the West Coast area. Many factors were taken into account to generate the initial map for suitable sites through GIS based analysis. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 27 publications
0
7
0
Order By: Relevance
“…MCDA approaches are increasingly supported or coupled with numerical modeling to provide more detailed and quantitative assessment of MAR opportunities and impacts (Sallwey et al., 2019; Zhang et al., 2019). Among the existing studies, Russo et al.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…MCDA approaches are increasingly supported or coupled with numerical modeling to provide more detailed and quantitative assessment of MAR opportunities and impacts (Sallwey et al., 2019; Zhang et al., 2019). Among the existing studies, Russo et al.…”
Section: Introductionmentioning
confidence: 99%
“…Zhang et al. (2019) conducted a GIS‐based MCDA analysis to determine suitable MAR sites along the West Coast of South Africa. They used MODFLOW and particle tracking (MODPATH) to trace the recharged water and concluded that the GIS analysis alone did not necessarily identify the most suitable sites.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Numerical modelling and hydro-geochemical investigations were often used by scientists to estimate aquifer storage or to carry out groundwater recovery based on exploratory simulations and scenarios development [8,9,[21][22][23][24]. They can also help to estimate the potential benefits for constructed structures on hydrologic conditions under a range of management scenarios.…”
Section: Introductionmentioning
confidence: 99%